Analysis of Generation Z Consumer Behavior in Online Purchases: Purchase Habits and Brand Preferences in the Digital Era - Desti, Yolanda; Sakinah, Yozi Putri; Damayanti, Nora (Journal of Economics and Management Scienties, 2025)
This study explores the influence of Digital Information Access, Customer Reviews, and Digital Marketing on Purchase Habits and Brand Preference among Generation Z consumers in Indonesia’s online shopping environment. Using a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM), data were collected from 213 respondents aged 18 to 26 who actively shop online. The results indicate that all three independent variables significantly influence Purchase Habits, with Digital Marketing showing the strongest effect. However, only Customer Reviews and Digital Marketing significantly impact Brand Preference, while Digital Information Access does not. These findings suggest that habitual purchasing behavior is primarily driven by informational convenience, while brand preference formation is more influenced by emotional and social engagement. The study contributes theoretically by integrating cognitive and affective dimensions of digital consumer behavior and practically by offering insights into strategic digital marketing tailored to Generation Z. Recommendations for further research include exploring mediating factors such as trust or social identity and conducting cross-generational comparisons to enrich understanding of evolving consumer dynamics in digital ecosystems.